Descriptive analysis of the ‘relictual’ Mediterranean landscape in the Guadalquivir River valley (southern Spain): a baseline for scientific research and the development of conservation action plans - Aparicio, Abelardo (Biodiversity and Conservation, 2007)
Landscape fragmentation is ancient and severe in the countryside of the Guadalquivir river valley (Western Andalusia, Southern Spain). BIANDOCC is a project that aims to inventory all the forest patches embedded in this anthropogenic area to record quantitative, qualitative, and descriptive information about management, conservation status, vegetation physiognomy and Xoristic richness. We have characterized a ‘relictual’ landscape (t1% of habitat retention) where nearly 70% of the patches (N = 535) are owned by private landowners who manage them to harvest pine nuts, cork, and Wrewood, for coal making, cattle raising, and to a lesser extent, beekeeping and agriculture. The publicly owned patches are intensively used for recreation. As a consequence, the vegetation physiognomy and conservation status in most forest stands is impoverished, with low shrub diversity and coverage and none or very low natural tree regeneration. Furthermore, patch size, connectedness and patch fractal dimension (i.e. microhabitat diversity) are all very low. However, the botanic richness is worth mentioning: 1,032 plant taxa have been identiWed, of which 70 are catalogued in an oYcial red list, 39 are relevant chorological novelties, and one was newly described for science. Therefore, and interestingly, the remnant forest patches in the studied area can be regarded as relevant biodiversity reservoirs. The project reported here constitutes an important baseline for developing true conservation action plans and provides an opportunity to address the potential ecological and biological eVects of fragmentation to plant genes, species, populations and communities, at the regional scale of the study, which are enhanced by the emergent landscape genetics and landscape ecology analytical tools.
Keywords: Biodiversity; Connectivity; fragstats; Habitat fragmentation; habitat loss; isolation; Mediterranean vegetation

Descriptive analysis of the ‘relictual’ Mediterranean landscape in the Guadalquivir River valley (southern Spain): a baseline for scientific research and the development of conservation action plans - Aparicio, Abelardo (Biodiversity and Conservation, 2007)
Landscape fragmentation is ancient and severe in the countryside of the Guadalquivir river valley (Western Andalusia, Southern Spain). BIANDOCC is a project that aims to inventory all the forest patches embedded in this anthropogenic area to record quantitative, qualitative, and descriptive information about management, conservation status, vegetation physiognomy and Xoristic richness. We have characterized a ‘relictual’ landscape (t1% of habitat retention) where nearly 70% of the patches (N = 535) are owned by private landowners who manage them to harvest pine nuts, cork, and Wrewood, for coal making, cattle raising, and to a lesser extent, beekeeping and agriculture. The publicly owned patches are intensively used for recreation. As a consequence, the vegetation physiognomy and conservation status in most forest stands is impoverished, with low shrub diversity and coverage and none or very low natural tree regeneration. Furthermore, patch size, connectedness and patch fractal dimension (i.e. microhabitat diversity) are all very low. However, the botanic richness is worth mentioning: 1,032 plant taxa have been identiWed, of which 70 are catalogued in an oYcial red list, 39 are relevant chorological novelties, and one was newly described for science. Therefore, and interestingly, the remnant forest patches in the studied area can be regarded as relevant biodiversity reservoirs. The project reported here constitutes an important baseline for developing true conservation action plans and provides an opportunity to address the potential ecological and biological eVects of fragmentation to plant genes, species, populations and communities, at the regional scale of the study, which are enhanced by the emergent landscape genetics and landscape ecology analytical tools.
Keywords: Biodiversity; Connectivity; fragstats; Habitat fragmentation; habitat loss; isolation; Mediterranean vegetation

Area effect on bird communities, guilds and species in a highly fragmented forest landscape of central Italy - Frank, Beatrice; Battisti, Corrado (Italian Journal of Zoology, 2005)
Abstract Breeding bird communities in an ?archipelago? of 16 wood fragments (13 oak deciduous woods, 1 holm wood, and 2 anthropogenic pinewoods) in a littoral plain of Central Italy were studied. Species richness and diversity index resulted directly and significantly correlated to fragment area. Species richness tended to cumulate in fragments over 100?ha area size. The log?transformed species/area relationship showed a coefficient z = 0.21, inside the range known for ecological islands. Z coefficient increased (0.23) excluding one guild of field?edge and anthropophilous species. Cluster analysis showed a separation among fragments based on their area size. Although species richness in pinewood plantations corresponded to the expected one from species/area relationship, cluster analysis highlighted disaffinity with bird communities of larger woods of oaks. These anthropogenic woods could not be surrogate habitats for many forest species in fragmented landscapes. Richness and abundance of field?edge and anthropophilous species resulted inversely correlated to fragment area. The opposite trend was observed for forest sensu latu species. Correlation coefficient increased considering only deciduous oak fragments. Some forest generalist species showed an abundance directly correlated to fragment size area (Troglodytes troglodytes, Erithacus rubecula, Fringilla coelebs); other species (Streptopelia turtur, Upupa epops, Jynx torquilla, Picoides major, Sitta europaed) were absent in fragment smaller than 10 ha. These species could constitute a set of area?sensitive taxa for planning strategy in highly fragmented landscapes, although, selection of these targets appears strongly context?limited.
doi: 10.1080/11250000509356689
Keywords: Area size effect; Area-sensitivity; Habitat fragmentation; Island biogeography; isolation; Target species; Threshold values

Area effect on bird communities, guilds and species in a highly fragmented forest landscape of central Italy - Frank, Beatrice; Battisti, Corrado (Italian Journal of Zoology, 2005)
Abstract Breeding bird communities in an ?archipelago? of 16 wood fragments (13 oak deciduous woods, 1 holm wood, and 2 anthropogenic pinewoods) in a littoral plain of Central Italy were studied. Species richness and diversity index resulted directly and significantly correlated to fragment area. Species richness tended to cumulate in fragments over 100?ha area size. The log?transformed species/area relationship showed a coefficient z = 0.21, inside the range known for ecological islands. Z coefficient increased (0.23) excluding one guild of field?edge and anthropophilous species. Cluster analysis showed a separation among fragments based on their area size. Although species richness in pinewood plantations corresponded to the expected one from species/area relationship, cluster analysis highlighted disaffinity with bird communities of larger woods of oaks. These anthropogenic woods could not be surrogate habitats for many forest species in fragmented landscapes. Richness and abundance of field?edge and anthropophilous species resulted inversely correlated to fragment area. The opposite trend was observed for forest sensu latu species. Correlation coefficient increased considering only deciduous oak fragments. Some forest generalist species showed an abundance directly correlated to fragment size area (Troglodytes troglodytes, Erithacus rubecula, Fringilla coelebs); other species (Streptopelia turtur, Upupa epops, Jynx torquilla, Picoides major, Sitta europaed) were absent in fragment smaller than 10 ha. These species could constitute a set of area?sensitive taxa for planning strategy in highly fragmented landscapes, although, selection of these targets appears strongly context?limited.
doi: 10.1080/11250000509356689doi: 10.1080/11250000509356689The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Area size effect; Area-sensitivity; Habitat fragmentation; Island biogeography; isolation; Target species; Threshold values

Factors affecting bird communities in fragments of secondary pine forests in the north-western Mediterranean basin - Brotons, L.; Herrando, S. (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2001)
We assessed the influence of size, extent of isolation and vegetation structure of secondary forest fragments on the richness and species composition of breeding bird communities in a sample of pine forest fragments surrounded by an agricultural matrix in the north-western Mediterranean basin. Fragment size was the main predictor of bird's occurrence, since it accounted for 70 % of the model variation. Isolation was also a valuable predictor of species occurrence, especially for forest specialists. Finally, subarboreal vegetation such as holm oak and a well-developed tree layer of large pines favoured forest species occurrence. Therefore, in spite of the long history of human impact, forest birds in Mediterranean mosaics are sensitive to both habitat loss and isolation of remnant patches in a similar manner to the patterns found in other temperate fragmented landscapes where human impact is more recent. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: birds; fragmentation; isolation; Mediterranean mosaics; vegetation structure

Factors affecting bird communities in fragments of secondary pine forests in the north-western Mediterranean basin - Brotons, L; Herrando, S (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2001)
We assessed the influence of size, extent of isolation and vegetation structure of secondary forest fragments on the richness and species composition of breeding bird communities in a sample of pine forest fragments surrounded by an agricultural matrix in the north-western Mediterranean basin. Fragment size was the main predictor of bird's occurrence, since it accounted for 70 % of the model variation. Isolation was also a valuable predictor of species occurrence, especially for forest specialists. Finally, subarboreal vegetation such as holm oak and a well-developed tree layer of large pines favoured forest species occurrence. Therefore, in spite of the long history of human impact, forest birds in Mediterranean mosaics are sensitive to both habitat loss and isolation of remnant patches in a similar manner to the patterns found in other temperate fragmented landscapes where human impact is more recent. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: birds; fragmentation; isolation; Mediterranean mosaics; vegetation structure

Genetic variation in central and marginal populations of Quercus suber L. - Jimenez, P; Agundez, D; Alia, R; Gil, L (SILVAE GENETICA, 1999)
Eighteen spontaneous populations of cork oak (Quercus suber) from Spain (14), Portugal (1), Morocco (1) and Italy (2), were surveyed at 14 loci from 12 enzyme systems. Percentage of polymorphic loci (64%), mean number of alleles (2.07), and mean expected heterozygosity (0.158) values were within the ranges described for the genus. Populations from the central range of the species and from peripheral areas were evaluated, and differences between these two kinds were assessed. Significant lower diversity (number of alleles and expected heterozygosity) was found for the most isolated and small size populations in contrast to central forests, showing the existence of mechanisms maintaining the levels of diversity even in some ;isolated stands. Interpopulation diversity (F-st) is 3.3%, indicating extensive gene flows or recent postglacial expansion. A possible recent bottleneck is detected in two populations by comparing actual with expected heterozygosity from the number of detected alleles.
Keywords: Genetic Variation; isolation; isozymes; marginal populations.; Quercus suber

Fungal endophytes in leaves, twigs and bark of Quercus ilex from Central Spain - Collado, J.; Platas, G.; Pelaez, F. (NOVA HEDWIGIA, 1996)
Fungal endophytes were isolated from leaves, twigs and bark discs of the main stem of 16 individuals of Quercus ilex at two sites in the forests of El Pardo, Madrid, central Spain. From 512 segments of each sample type, 1084 fungal isolates were obtained, distributed among 98 species of filamentous fungi, yielding about 21 species/tree. Four isolation media were tested, which showed different behaviour depending on the type of sample. The use of fungitoxic compounds, such as benomyl or cycloheximide, resulted in a decrease in the number of isolates and species recovered, especially from leaves. Most of the dominant fungal species were not isolated from the four media indistinctly, but were preferentially recovered from one of the media. Twigs exhibited a higher degree of fungal infection than bark discs and leaves. The mycota isolated from bark and twigs were more similar to each other than to the fungal populations recovered from leaves. The frequency of isolation of most of the dominant fungal species depended significantly upon the sample type. A Phoma sp. was the only taxon similarly distributed among the three sample types. The height from which the bark discs were removed also influenced the population recovered. Both sampling sites were similar with respect to the number of species recovered from twigs and bark discs, but differed in the number of species from leaves. As in other plant and non-plant fungal communities, the population recovered from Q. ilex was characterized by a few species which accounted for most of the isolates, and a much larger number of species present with low frequencies. Five species (Nodulisporium sp., Acremonium strictum and three Phoma-like coelomycetes) represented more than 50% of the whole isolates. Coelomycetous anamorphs of ascomycetes bearing small, hyaline ameroconidia, were the most abundant group of fungi, whereas teleomorphs were rarely seen.
The following values have no corresponding Zotero field: pub-location: JOHANNESSTR 3A, D-70176 STUTTGART, GERMANY publisher: GEBRUDER BORNTRAEGER
Keywords: endophytes; isolation; microbial diversity; Quercus ilex

Fungal endophytes in leaves, twigs and bark of Quercus ilex from Central Spain - Collado, J; Platas, G; Pelaez, F (NOVA HEDWIGIA, 1996)
Fungal endophytes were isolated from leaves, twigs and bark discs of the main stem of 16 individuals of Quercus ilex at two sites in the forests of El Pardo, Madrid, central Spain. From 512 segments of each sample type, 1084 fungal isolates were obtained, distributed among 98 species of filamentous fungi, yielding about 21 species/tree. Four isolation media were tested, which showed different behaviour depending on the type of sample. The use of fungitoxic compounds, such as benomyl or cycloheximide, resulted in a decrease in the number of isolates and species recovered, especially from leaves. Most of the dominant fungal species were not isolated from the four media indistinctly, but were preferentially recovered from one of the media. Twigs exhibited a higher degree of fungal infection than bark discs and leaves. The mycota isolated from bark and twigs were more similar to each other than to the fungal populations recovered from leaves. The frequency of isolation of most of the dominant fungal species depended significantly upon the sample type. A Phoma sp. was the only taxon similarly distributed among the three sample types. The height from which the bark discs were removed also influenced the population recovered. Both sampling sites were similar with respect to the number of species recovered from twigs and bark discs, but differed in the number of species from leaves. As in other plant and non-plant fungal communities, the population recovered from Q. ilex was characterized by a few species which accounted for most of the isolates, and a much larger number of species present with low frequencies. Five species (Nodulisporium sp., Acremonium strictum and three Phoma-like coelomycetes) represented more than 50% of the whole isolates. Coelomycetous anamorphs of ascomycetes bearing small, hyaline ameroconidia, were the most abundant group of fungi, whereas teleomorphs were rarely seen.
Keywords: endophytes; isolation; microbial diversity; Quercus ilex